À table ! De l'approvisionnement au dernier repas - Bacoup, Paul; Caurette, Natacha; Laurent, Anne-Sophie; Marty, Astrid (Archéo.doct, 2021)
This newest issue of Archéo.doct is a compilation of the discussions that took place during the 15th "Journée Doctorale" of the ED 112 of Paris 1 Panthéon-Sorbonne University. This event was titled "À Table ! De l'approvisionnement au dernier repas. Regards croisés sur l'archéologie de l'alimentation". Central to the current scientific landscape in social sciences, this subject allowed for multi-disciplinary discussions on various matters, from food storage in the Aegean Prehistory to the social relations between humankind and printed food in contemporary times, throughout the world. A diverse array of approaches in the study of food are herein presented, ranging from morphometric studies to scientific experimentation, and including the analysis of ethnographical, text or iconographic data. Through these approaches, the authors in this volume touch on the majority of questions relating to food, from the acquisition of foodstuffs to their consumption, without forgetting their political connotations and symbolic importance. It is then possible to get a grasp on the complexity of the role of food in human societies, beyond its function as physiological necessity.